Aphidiid Wasps (Hymenoptera, Aphidiidae) Parasitizing Aphids on Herbaceous Legumes (Fabaceae) in the Central Wood-and-Steppe Zone of Ukraine - Kaliuzhna, M.O.; Zubenko, O.G. (Вестник зоологии, 2013)
Species composition and host associations of the aphidiid wasps infesting aphids in Kyiv, Cherkasy, Poltava and Kirovohrad Regions of the Central Wood-and-Steppe Zone of Ukraine were studied during 2010–2011, mainly on meadows. Nine species of aphids were found on 36 plant species, of them 7 species were infested by aphidiids. Six species of parasites were reared: Lysiphlebus fabarum (Marshall), L. confusus Tremblay et Eady, L. fritzmuelleri Mackauer, Lipolexis gracilis Fцrster, Binodoxys acalephae (Marshall), B. angelicae (Haliday). The most widespread species were L. fabarum and L. confusus. The rate of aphids colony infestation according to weather conditions and association with host plants are discussed. An illustrated key to the found species is given.